Abnormal Spontaneous Gamma Power Is Associated With Verbal Learning and Memory Dysfunction in Schizophrenia - Tanaka-Koshiyama, Kumiko; Koshiyama, Daisuke; Miyakoshi, Makoto; Joshi, Yash B.; Molina, Juan L.; Sprock, Joyce; Braff, David L.; Light, Gregory A. (Frontiers in Psychiatry, 2020)
Background: Schizophrenia patients exhibit cognitive deficits across multiple domains, including verbal memory, working memory and executive function, which substantially contribute to psychosocial disability. Gamma oscillations are associated with a wide range of cognitive operations, and are important for cortico-cortical transmission and the integration of information across neural networks. While previous reports have shown that schizophrenia patients have selective impairments in the ability to support gamma oscillations in response to 40-Hz auditory stimulation, it is unclear if patients show abnormalities in gamma power at rest or whether resting-state activity in other frequency bands is associated with cognitive functioning in schizophrenia patients. Methods: Resting-state electroencephalogram (EEG) was assessed over 3 minutes in 145 healthy comparison subjects and 157 schizophrenia patients. Single-word reading ability was measured via the Reading subtest of the Wide Range Achievement Test-3 (WRAT). Auditory attention and working memory were evaluated using Letter-Number Span and Letter-Number Sequencing. Executive function was assessed via perseverative responses on the Wisconsin Card Sorting Test (WCST). Verbal learning performance was measured using the California Verbal Learning Test second edition (CVLT-II). Results: Schizophrenia patients showed normal levels of delta-band power but abnormally elevated EEG power in theta, alpha, beta and gamma bands. An exploratory correlation analysis showed a significant negative correlation of gamma-band power and verbal learning performance in schizophrenia patients. Conclusions: Patients with schizophrenia have abnormal resting-state EEG power across multiple frequency bands; gamma-band abnormalities were selectively and negatively associated with impairments in verbal learning. Resting-state gamma-band EEG power may be useful for understanding the pathophysiology of cognitive dysfunction and developing novel therapeutics in schizophrenia patients.